(untitled) (Élisée - Revista de Geografia da UEG, 2022)
This article aims to evaluate the relationship between land use and influenced by relief in the municipality of Niquelândia. For that, surveys of several databases were carried out such as: Maps of relief and cover and land use, which were processed using data processing techniques in the GIS. The municipality has a diversified economy, the most notable are: mining, agriculture, services and more recently the tourism market has taken over, mainly focused on fishing tourism on Lake Serra da Mesa. The Cerrado biome in the municipality is partially preserved in the areas of greater relief and at higher altitudes, it is possible to perceive the intrinsic influence of geomorphology in the preservation of the biome and in contrast in the use and occupation of the soil. This is reflected in the use of the flatter areas for agriculture and urban occupation.